1965
DOI: 10.1037/h0022522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of threat in a performance appraisal interview.

Abstract: Real-life appraisal interviews conducted by 92 manager-subordinate pairs were studied intensively. Reactions of subordinates were systematically obtained before and after their appraisal interviews and the proceedings in the actual interviews were carefully documented by trained observers. Measures of subsequent performance improvement realized as a result of the appraisal interviews were taken 12 wks later The results indicated that a manager's attempts to assist a subordinate by pointing up improvement needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
2

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 3 publications
0
45
2
Order By: Relevance
“…Only in the experiment by Morse & Reimer (1956) was there a consistent pattern of statistically significant results showing that manipulation of participation affected employee satisfaction. French, Israel & As (1960) found significant changes on only three out of fourteen measures, while Kay, French & Meyer (1962) and Juralewicz (1974) did not obtain any at all. In the remaining field experiments (Coch & French, 1948;Lawler & Hackman, 1969) reliance was placed entirely on the impressions of the investigators and there is no guarantee that participants would have described their feelings in the same way.…”
Section: The Fall Of Industrial Democracymentioning
confidence: 92%
See 1 more Smart Citation
“…Only in the experiment by Morse & Reimer (1956) was there a consistent pattern of statistically significant results showing that manipulation of participation affected employee satisfaction. French, Israel & As (1960) found significant changes on only three out of fourteen measures, while Kay, French & Meyer (1962) and Juralewicz (1974) did not obtain any at all. In the remaining field experiments (Coch & French, 1948;Lawler & Hackman, 1969) reliance was placed entirely on the impressions of the investigators and there is no guarantee that participants would have described their feelings in the same way.…”
Section: The Fall Of Industrial Democracymentioning
confidence: 92%
“…However, there have been a few experimental studies in which the amount of participation has been deliberately manipulated (e.g., Coch & French, 1948;French Israel & As, 1960;Morse & Reimer, 1956;Juralewicz, 1974;Kay, French & Meyer, 1962;Lawler & Hackman, 1969).…”
Section: The Fall Of Industrial Democracymentioning
confidence: 99%
“…Establishing goals for the subordinate to achieve on the job during the interview has been found to result in several positive outcomes such as greater subordinate satisfaction and perceived accuracy of the evaluation (Landy, Barnes, & Murphy, 1978), perceived fairness (Burke, Weitzel, & Weir, 1978;Landy, Barnes, & Murphy, 1978), perceived utility of the interview (Greller, 1978), mutual understanding (Burke, Weitzel, & Weir, 1978) and subordinate desire to improve as well as actual improvement (Burke, Weitzel, & Weir, 1978;Burke & Wilcox, 1969). Interviewer criticism resulted in greater defensiveness, more negative attitudes toward appraisals and less improvement in subordinate performance (Kay, Meyer, & French, 1965). However, when the criticism was revised into goals, greater subordinate performance resulted (French, Kay, & Meyer, 1966).…”
Section: Research On Performance Appraisal Interviewsmentioning
confidence: 94%
“…For instance, Nemeroff and Wexley (1977) found that praise by the superior correlated positively with subordinate satisfaction with the interview and motivation to improve. However, Kay, Meyer and French (1965) discovered that praise would not have positive effects if subordinates perceive it to simply condition them for criticism to follow. Holloway and Wampold (1983) found that superiors devalued themselves and their subordinates for excessive use of supportive communication and did not find it to positively influence any of the subordinate's judgments about the interview.…”
Section: Research On Performance Appraisal Interviewsmentioning
confidence: 96%
See 1 more Smart Citation